Upaya Pemerintah Melalui Otoritas Jasa Keuangan Dalam Pengawasan Fintech Berbasis Peer To Peer Lending Yang Merugikan Pemberi Pinjaman Atas Wanprestasi Perjanjian Fintech Berbasis Peer To Peer Lending Yang Mengalami Gagal Bayar Dan Perlindungan Hukum Terh - Mohammad Alwi Abizar; Devi Siti Hamzah Marpaung (Jurnal Ilmiah Wahana Pendidikan, 2022)
The government's efforts through financial services authorities in supervising fintech based on peer to peer lending that harm lenders for default of fintech agreements based on peer to peer lending that have failed to pay and legal protection for lenders The nature of this research is descriptive analysis because this study is intended to provide data that be as thorough as possible about the problems discussed and analyze the data obtained to answer the problems. This research approach uses a statutory approach and a case-by-case approach. A normative juridical approach is used to find out all legal provisions, especially the protection of fintech service users in Indonesia. A case-by-case approach for the purpose of studying legal standards or rules applied in legal practice. The need for a new law on Fintech Peer To Peer Lending so that the public does not experience confusion with what is called Fintech Peer To Peer Lending and that law enforcement can be done better.